Comparison of Single- and Repeated-Ischemia-Induced Changes in Expression of Flip and Flop Splice Variants of AMPA Receptor Subtypes GluR1 and GluR2 in the Rats Hippocampus CA1 Subregion - Izzettin Hatip-; Katsunori Iwasaki; Nobuaki Egashira; Daisuke Ishibashi; Kenichi Mishima; Michihiro Fujiwara (Elsevier, 2007)
In addition to their role in physiological activities, ionotropic glutamate α-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptors (AMPARs) play an important role in neuronal death, especially that following ischemic insults. In this study, we examined the effect of single (SI) and twice repeated (RI)-4-vessel occlusion-ischemia on rat performance in the 8-armed radial maze test. Moreover, the effects of SI and RI on the AMPARs subunits glutamate receptor (GluR) 1 and GluR2 flip and flop variants composition in the CA1 subregion of the hippocampus were investigated using RT-PCR, normalized to glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and expressed as their ratios to the latter. The results showed that SI and RI impaired the maze performance by decreasing correct choices and increasing the error choices, but RI increased error choices to a greater extent than the SI. The SI reduced only GluR1 flip/GAPDH on day 1. The SI did not alter ratios of GluR2 variants to those of GluR1. On the other hand, the RI decreased GluR2 flip and flop variants after 1 and 3 days, respectively, whereas after 7 days, it increased the flip variant of both GluR1 and GluR2. Moreover, the RI reduced ratios of GluR2 variants to those of GluR1. These results reveal the differential effects of the SI and RI on memory and expression of the AMPARs subunits GluR1 and GluR2 and their flip and flop variants in the CA1. Keywords:: AMPA GluR1 GluR2 flip and flop, hippocampus CA1, single- and repeated-ischemia, memory, Alzheimer's disease